Research progress of diabetic retinopathy and gut microecology - Wang, Rui; Wang, Qiu-Yuan; Bai, Yang; Bi, Ye-Ge; Cai, Shan-Jun (Frontiers in Microbiology, 2023)
According to the prediction of the International Diabetes Federation, global diabetes mellitus (DM) patients will reach 783.2 million in 2045. The increasing incidence of DM has led to a global epidemic of diabetic retinopathy (DR). DR is a common microvascular complication of DM, which has a significant impact on the vision of working-age people and is one of the main causes of blindness worldwide. Substantial research has highlighted that microangiopathy and chronic low-grade inflammation are widespread in the retina of DR. Meanwhile, with the introduction of the gut-retina axis, it has also been found that DR is associated with gut microecological disorders.The disordered structure of the GM and the destruction of the gut barrier result in the release of abnormal GM flora metabolites into the blood circulation. In addition, this process induced alterations in the expression of various cytokines and proteins, which further modulate the inflammatory microenvironment, vascular damage, oxidative stress, and immune levels within the retina. Such alterations led to the development of DR. In this review, we discuss the corresponding alterations in the structure of the GM flora and its metabolites in DR, with a more detailed focus on the mechanism of gut microecology in DR. Finally, we summarize the potential therapeutic approaches of DM/DR, mainly regulating the disturbed gut microecology to restore the homeostatic level, to provide a new perspective on the prevention, monitoring, and treatment of DR.